Bitterblue - Cashore, Kristin (CPI Group (UK) Ltd, 2013)
Eighteen-year-old Bitterblue, queen of Monsea, realizes her heavy responsibility and the futility of relying on advisors who surround her with lies as she tries to help her people to heal from the thirty-five-year spell cast by her father, a violent psychopath with mind-altering abilities.